Butylated Hydroxytoluene analogs: synthesis and evaluation of their multipotent antioxidant activities - Ariffin, Azhar; Ng, S.W.; Yehye, W.A.; Rahman, N.A.; Alhadi, A.A.; Khaledi, H. (2012)
A computer-aided predictions of antioxidant activities were performed with the Prediction Activity Spectra of Substances (PASS) program. Antioxidant activity of compounds 1, 3, 4 and 5 were studied using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and lipid peroxidation assays to verify the predictions obtained by the PASS program. Compounds 3 and 5 showed more inhibition of DPPH stable free radical at 10(-4) M than the well-known standard antioxidant, butylated hydroxytoluene (BHT). Compound 5 exhibited promising in vitro inhibition of Fe2+-induced lipid peroxidation of the essential egg yolk as a lipid-rich medium (83.99%, IC50 16.07 +/- 3.51 mu M/mL) compared to alpha-tocopherol (alpha-TOH, 84.6%, IC50 5.6 +/- 1.09 mu M/mL). The parameters for drug-likeness of these BHT analogues were also evaluated according to the Lipinski's "rule-of-five" (RO5). All the BHT analogues were found to violate one of the Lipinski's parameters (LogP > 5), even though they have been found to be soluble in protic solvents. The predictive polar surface area (PSA) and absorption percent (% ABS) data allow us to conclude that they could have a good capacity for penetrating cell membranes. Therefore, one can propose these new multipotent antioxidants (MPAOs) as potential antioxidants for tackling oxidative stress and lipid peroxidation processes.